Effects of Rifampin on the Pharmacokinetics of a Single Dose of Istradefylline in Healthy Subjects. (7th September 2017) - Mukai, Mayumi; Uchimura, Tatsuo; Zhang, Xiaoping; Greene, Douglas; Vergeire, Maria; Cantillon, Marc
Abstract: Istradefylline, a selective adenosine A2A inhibitor, is under development for the treatment of Parkinson's disease. The effect of oral steady‐state rifampin 600 mg/day, a potent cytochrome P450 (CYP) 3A4 inducer, on the disposition of a single oral dose of istradefylline 40 mg was determined in a crossover study in 20 healthy subjects by measuring plasma concentrations of istradefylline and its M1 and M8 metabolites and their derived pharmacokinetic parameters. Based on the geometric mean ratio of log‐transformed data, rifampin reduced istradefylline exposure: Cmax, 0.55 (90%CI, 0.49–0.62); AUClast, 0.21 (90%CI, 0.19–0.22); and AUCinf, 0.19 (90%CI, 0.18–0.20), indicating nonequivalence. These changes were primarily because of the effect of rifampin on the elimination parameters of istradefylline; mean CL/F was increased from 4.0 to 20.6 L/h, and mean t1/2 was reduced from 94.8 to 31.5 hours. The effect of rifampin coadministration on the disposition of the istradefylline M1 and M8 metabolites was inconsistent and variable. Furthermore, as exposure of the istradefylline M1 and M8 metabolites in plasma was generally <9% of total drug exposure, it would be expected to have a negligible impact on the pharmacodynamic effect of istradefylline. Caution should be exercised when istradefylline is administered concurrently with strong CYP3A4 inducers and dose adjustment considered.